Theory for polymer analysis using nanopore-based single-molecule mass spectrometry - Reiner, Joseph E. (National Academy of Sciences, 2010)
Nanometer-scale pores have demonstrated potential for the electrical detection, quantification, and characterization of molecules for biomedical applications and the chemical analysis of polymers. Despite extensive research in the nanopore sensing field, there is a paucity of theoretical models that incorporate the interactions between chemicals (i.e., solute, solvent, analyte, and nanopore). Here, we develop a model that simultaneously describes both the current blockade depth and residence times caused by individual poly(ethylene glycol) (PEG) molecules in a single α-hemolysin ion channel. Modeling polymer-cation binding leads to a description of two significant effects: a reduction in the mobile cation concentration inside the pore and an increase in the affinity between the polymer and the pore. The model was used to estimate the free energy of formation for K(+)-PEG inside the nanopore (≈-49.7 meV) and the free energy of PEG partitioning into the nanopore (≈0.76 meV per ethylene glycol monomer). The results suggest that rational, physical models for the analysis of analyte-nanopore interactions will develop the full potential of nanopore-based sensing for chemical and biological applications.